DISTRIBUTION OF PEOPLE’S BUSINESS CREDIT (KUR) IN INDONESIA: IDENTIFYING MISTARGETING PHENOMENA DUE TO ADVERSE SELECTION - Nyoman Diah Praba Anggari; I Wayan Sukadana (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The People’s Business Credit (KUR) is a subsidized financing instrument initiated by the Indonesian government aimed at increasing access to capital for eligible but unbankable entrepreneurs. However, in practice, the distribution of KUR still faces targeting challenges due to adverse selection, which arises from information asymmetry among the government, financial institutions, and borrowers. This study aims to identify the presence of adverse selection in KUR distribution across Indonesia, which potentially leads to mistargeting in the subsidized credit market. The study utilizes data from the March 2024 National Socio-Economic Survey (SUSENAS) with a total sample of 65,535 households. The analysis employs binary logistic regression, simultaneous testing, partial testing, and marginal effect estimation. Data collection was conducted using a non-participant observation technique. The results indicate that all research variables—business ownership, region, savings account ownership, asset ownership, main income source, and occupation—simultaneously have a significant effect on the probability of a household becoming a KUR recipient. The findings also reveal that access to KUR, particularly for micro and small enterprises (MSEs), remains limited despite being the primary target of the program. Furthermore, the presence of adverse selection is identified, wherein households with existing assets are more likely to obtain KUR financing. This highlights the need for policy reforms in the KUR distribution mechanism to ensure that eligible productive businesses without additional collateral can access financing in a fair and inclusive manner across all regions of Indonesia.